SCIENTIFIC AND CREATIVE PORTRAIT OF THE ACADEMY OF ARCHITECTURE AND ARTS - Alexandr M. Boyarinov; Viktoriya V. Pischulina (Высшее образование в России, 2016)
The article describes the main lines of pedagogical, research and creative work of SFEDU academy of architecture and arts. The basic principle of its activity is the development of individual creative faculties and formation of the abilities in conceptual comprehension and modeling of the environment in a context of regionalization and globalization of cultures. This principle reflects environmental approach to scientific research, which requires modeling of regional problems of architecture, design, and art in a context of global processes. The corner stone of the organization of the educational process is “learning through real designing and creative work”.